Penyerapan Logam Krom dalam Limbah Cair Laboratorium Kimia Menggunakan Adsorben Tanah Napa - Mawardi Anwar; Hary Sanjaya; Victoria Frisiananda (Jurnal Periodic Jurusan Kimia UNP, 2013)
It has been investigated the adsorbtion of chrom metal in chemistry laboratory liquid waste using tanah napa as an adsorbent. Waste containing chrom metal was pass through a coloum that filled with tanah napa adsorbent. It is studied the use of nitrit acid (HNO3) for regeneration purpose and recovery of chrom metal at various concentration. The result showed that HNO3 at concentration 0.4M was the best for regeneration of Chrom(III) is 78.03% and concentration 0.3M for regeneration of Chrom(VI) is 53.02%. The optimum condition of this method were applied to preconcentration of Chrom in chemistry laboratory liquid waste with HNO3 0.3M. The result show that Chrom found in chemistry laboratory liquid waste which is initially 0.9123 ppm can be preconcentration to 1.7760 ppm with 5x10mL preconcentration.